Spatial density of open chromatin: an effective metric for the functional characterization of topologically associated domains. Issue 3 (28th September 2020) - Jiang, Shuai; Li, Hao; Hong, Hao; Du, Guifang; Huang, Xin; Sun, Yu; Wang, Junting; Tao, Huan; Xu, Kang; Li, Cheng; Chen, Yang; Chen, Hebing; et al.
Abstract: Topologically associated domains (TADs) are spatial and functional units of metazoan chromatin structure. Interpretation of the interplay between regulatory factors and chromatin structure within TADs is crucial to understand the spatial and temporal regulation of gene expression. However, a computational metric for the sensitive characterization of TAD regulatory landscape is lacking. Here, we present the spatial density of open chromatin (SDOC) metric as a quantitative measurement of intra-TAD chromatin state and structure. SDOC sensitively reflects epigenetic properties and gene transcriptional activity in TADs. During mouse T-cell development, we found that TADs with decreased SDOC are enriched in repressed developmental genes, and the joint effect of SDOC-decreasing and TAD clustering corresponds to the highest level of gene repression. In addition, we revealed a pervasive preference for TADs with similar SDOC to interact with each other, which may reflect the principle of chromatin organization.